INTERACTIVE VIDEO PROJECT TO BOOST UNIVERSITY STUDENTS’ SELF-CONFIDENCE IN ENGLISH PUBLIC SPEAKING - Ni Putu Intan Permatasari (Universitas PGRI Palembang, 2024)
English language proficiency has become essential for those pursuing higher education in our fast-paced environment. A growing demand for jobs in the global workplace is coming from English speakers in particular. For many students, especially those who are non-native speakers of the language, public speaking in English presents a considerable difficulty. This research investigated the effects of an interactive video project on students' public speaking confidence in English. The middle and final exams for students were designed to include project-based learning in addition to classroom activities. In order to receive constructive comments from their lecturer and fellow students, students in this project had to produce and deliver videos on the prescribed themes. In this study, 20 students who had completed an interactive video project for class and the semester exam in Regular English at Universitas Pendidikan Nasional (Undiknas University) Denpasar, Bali, participated in a semi-structured interview and observation of the classroom during a descriptive qualitative approach. This study's conclusions showed that students' self-assessed confidence in their ability to give English public speeches or presentations can significantly increase as a result of the interactive video project. A process of iterative production, presentation, and feedback was combined with the interactive project. Students had an entertaining chance to hone and polish their speaking abilities with the interactive video project.